2016
DOI: 10.1016/j.ijggc.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of CO2-enhanced oil recovery in Ohio: Implications for carbon capture, utilization, and storage in the Appalachian Basin region

Abstract: A cost-benefit analysis is presented to evaluate the economic feasibility of carbon dioxide (CO 2)enhanced oil recovery (EOR) in Ohio. Ohio-specific data is integrated with reservoir performance and economic models to define the analysis framework. The analysis is applied to two Ohio oil fields to illustrate how the methodology can be used to constrain project economics and profitability. The regression derived from the CO 2 break-even price calculated for a range of oil prices indicates that the change in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The cumulative cost-effective oil production varied between 0.3 and 1.3 billion tons (2.1 and 9.1 billion barrels). This is consistent with research reported from Appalachian basin region, which suggests that CO 2 -EOR may be economically feasible in the study area when oil prices are $70/STB or higher [28,32]. However, the economics of onshore CO 2 -EOR will face an undesirable impact due to complex geological properties, high viscosity of crude oil, high royalty rates, technology limitations, and the lack of incentives for CO 2 -EOR projects.…”
Section: Mechanisms Of Co 2 Injection For Eorsupporting
confidence: 87%
See 1 more Smart Citation
“…The cumulative cost-effective oil production varied between 0.3 and 1.3 billion tons (2.1 and 9.1 billion barrels). This is consistent with research reported from Appalachian basin region, which suggests that CO 2 -EOR may be economically feasible in the study area when oil prices are $70/STB or higher [28,32]. However, the economics of onshore CO 2 -EOR will face an undesirable impact due to complex geological properties, high viscosity of crude oil, high royalty rates, technology limitations, and the lack of incentives for CO 2 -EOR projects.…”
Section: Mechanisms Of Co 2 Injection For Eorsupporting
confidence: 87%
“…When the condensation/ vaporization process proceeds further downstream, the gas becomes more enriched due to contact with the oil. And the enrichment is said to occur at the point where the gas "nearly" becomes miscible with the original reservoir oil, ensuring a more efficient displacement process, even though miscibility is never fully developed (i.e., the two phases are never fully miscible in all proportions) [20,[27][28][29]. CO 2 is not miscible with most crude oils at first contact under normal reservoir conditions.…”
Section: Vaporizing Gas Drive Mechanismmentioning
confidence: 99%
“…Although reservoir simulation for EOR operations in specific fields are not conducted here (as done by Dai et al 2016 83 and Fukai et al 2016 39 ), this model incorporates a randomized selection of plausible fields and production profiles for CO 2 -EOR and storage. This enables us to assess general conditions under which gigatonne-scale CCS deployment can occur by 2050.…”
Section: Discussionmentioning
confidence: 99%
“…These can either be centered around a producer (called normal) or an injector (called inverted). Here, MIICE assumes that all patterns are 5-spot inverted patterns with 1 injector and 4 producers as this is commonplace in CO 2 -EOR practice 39,40,56,58 . As a rule of thumb each pattern has a surface area of 40-acres and on a field-scale it is assumed that the ratio of producers to injectors is 1.8:1, which corresponds to nine adjacent 5-spot patterns.…”
Section: Co 2 Enhanced Oil Recoverymentioning
confidence: 99%
“…Experimental investigations and numerical reservoir simulations on binary systems including hydrocarbons and CO 2 were conducted to improve the hydrocarbon recovery (Bachu 2016 ; Bessières et al 2001 ; Diep et al 1998 ; Do and Pinczewski 1991 ; Fukai et al 2016 ; Jamali and Ettehadtavakkol 2017 ; Kim and Santamarina 2014 ; Kiran et al 1996 ; Kwak and Kim 2017 ; Li et al 2013a , 2015 ; Li and Fan 2015 ; Luo et al 2007 , 2013 ; Lv et al 2015 ; Mulliken and Sandler 1980 ; Shelton et al 2016 ; Yang and Gu 2005 ). Most of these studies investigated the oil swelling effect primarily as a result of CO 2 dissolution in the light fractions of oil.…”
Section: Introductionmentioning
confidence: 99%